Recuperação e purificação de proteínas do soro de queijo tipo coalho usando cromatografia de troca iônica e interação hidrofóbica em leito na forma expandida - Cavalcanti, Jorge dos Santos (2010)
Expanded Bed Adsorption plays an important role in the downstream processing mainly for reducing costs as well as steps besides could handling cells homogenates or fermentation broth. In this work Expanded Bed Adsorption was used to recover and purify whey proteins from coalho cheese manufacture using Streamline DEAE and Streamline SP both ionic resins as well as a hydrophobic resin Streamline Phenyl. A column of 2.6 cm inner diameter with 30 cm in height was coupled to a peristaltic pump. Hydrodynamics study was carried out with the three resins using Tris-HCl buffer in concentration of 30, 50 and 70 mM, with pH ranging from 7.0 to 8.0. In this case, assays of the expansion degree as well as Residence Time Distribution (RTD) were carried out. For the recovery and purification steps, a whey sample of 200 mL, was submitted to a column with 25mL of resin previously equilibrated with Tris/HCl (50 mM, pH 7.0) using a expanded bed. After washing, elution was carried out according the technique used. For ionic adsorption elution was carried out using 100 mL of Tris/HCl (50 mM, pH 7.0 in 1M NaCl). For Hydrophobyc interaction elution was carried out using Tris/HCl (50 mM, pH 7.0). Adsorption runs were carried out using the three resins as well as theirs combination. Results showed that for hydrodynamics studies a linear fit was observed for the three resins with a correlation coefficient (R2) about 0.9. In this case, Streamline Phenyl showed highest expansion degree reaching an expansion degree (H0/H) of 2.2. Bed porosity was of 0.7 when both resins Streamline DEAE and Streamline SP were used with StremLine Phenyl showing the highest bed porosity about 0.75. The number of theorical plates were 109, 41.5 and 17.8 and the axial dipersion coefficient (Daxial) were 0.5, 1.4 and 3.7 x 10-6 m2/s, for Streamline DEAE, Streamline SP and Streamline Phenyl, respectively. Whey proteins were adsorved fastly for the three resins with equilibrium reached in 10 minutes. Breakthrough curves showed that most of proteins stays in flowthrough as well as washing steps with 84, 77 and 96%, for Streamline DEAE, Streamline SP and Streamline Phenyl, respectively. It was observed protein peaks during elution for the three resins used. According to these peaks were identified 6 protein bands that could probably be albumin (69 KDa), lactoferrin (76 KDa), lactoperoxidase (89 KDa), β-lactoglobulin (18,3 KDa) e α-lactoalbumin (14 KDa), as well as the dimer of beta-lactoglobulin. The combined system compound for the elution of Streamline DEAE applied to the Streamline SP showed the best purification of whey proteins, mainly of the α-lactoalbumina